INSTAGRAM POST AS A PERSONAL BRANDING MEDIA TO BUILD IMAGE REPUTATION IN SOCIAL REALITY: (Assessed by Dramaturgy Theory) - Elvira Shinta Amelia (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
This study focuses on the use of Instagram posts as a personal branding medium to build image reputation in social reality. The problem raised in this study is how the results of using Instagram posts as a personal branding medium to form image reputation in social reality. The research method used is a qualitative descriptive method of phenomenology and sampling through snowball sampling and data collection techniques through interviews, documentation, and observation. The theory used in reviewing the problems raised in this research is the dramaturgical theory proposed by Erving Goffman and uses the theory proposed by Mcnally and Speak to see the basis for the formation of a strong personal branding, namely there are three basic things that must be met, including distinctiveness, relevance and consistency. The result of this research is that all informants play their roles on stage according to the role of the lifestyle they want to instill in the minds of followers. Meanwhile, backstage, it was found that all the informants had a more casual lifestyle. Based on the results of the study, it can be seen that there is an element of irrelevance from their personal branding, but the four informants still get a good image reputation in their social reality.Keywords: Instagram, personal branding, image reputation, social reality, dramaturgy